Rethinking the right to health: Ableism and the binary between individual and collective rights - Zimmer, Amie Leigh (Bioethics, 2021)
While universal healthcare provisions are the global norm rather than the exception, the United States exists in the latter category. The paradox remains that while the right to health is both increasingly implemented and recognized on a global scale, the United States seems to run farther away from the arguments and global examples that might pave its way. I suggest that an understanding of the imposition of healthcare as “coercive,” and hence as an impingement on individual agency, activates its criticism as an inhibition of freedom that in turn motivates the libertarianism at the heart of the dominant, market-based approach to health insurance provisions. At least one of the underlying assumptions of this view is that universal healthcare would impose or impinge on individual rights, and that such an impingement is a violation of autonomy. In this article, I aim to challenge this assumption by suggesting that the pitting of individual health rights against collective burdens stems in part from a related assumption of general health or welfare on the part of the collective: that disability and debility alike are anomalies or anomalous to the general health of the population. In other words, it will be my contention that individual health rights are only at odds with “collective rights” when the collective is perceived to be able-bodied.